Online One-Stop Shop for Disaster Response Services After the MH17 Airplane Crash: An Evaluation Study - van Herpen, Merel M.; Dückers, Michel L. A.; Schaap, Rick; Olff, Miranda; te Brake, Hans (Frontiers in Public Health, 2022)
Background A one-stop shop for disaster response services provides a central location for information and advice in an accessible way. Yet little is known about its organization and outcomes. After the MH17 airplane crash, the one-stop shop concept was realized through a digital environment called the Information and Referral Center (IRC). The aim of this study was to evaluate the experiences of users and providers in regard to the IRC and to identify improvement points for future IRCs. Method Data was collected among affected ones as well as involved organizations, using interviews, focus groups, surveys and online user information. Existing evaluation and quality models were combined to design the study and analyze the data. Results First, affected ones and a variety of organizations involved were positive about the merits of the IRC. Affected ones indicated they perceived the IRC as a reliable source of information and appreciated the referral possibilities. Second, the feature of the IRC to serve as a community where affected ones could meet, share experiences and support each other was hardly used according to participants. Lastly, tracking evolving psychosocial needs and problems through the IRC was hampered due to difficulty in accessing relevant data. Conclusions The IRC helped organizations to structure and align their services. Affected ones were positive about its reliability and accessibility. An IRC has to be embedded within the established care structures. Future research could indicate whether an IRC is useful in other event types and population contexts as well.